Mitochondrial Succinate Metabolism and Reactive Oxygen Species Are Important but Not Essential for Eliciting Carotid Body and Ventilatory Responses to Hypoxia in the Rat - Agnieszka Swiderska; Andrew M. Coney; Abdulaziz A. Alzahrani; Hayyaf S. Aldossary; Nikolaos Batis; Clare J. Ray; Prem Kumar; Andrew P. Holmes (MDPI AG, 2021)
Reflex increases in breathing in response to acute hypoxia are dependent on activation of the carotid body (CB)-A specialised peripheral chemoreceptor. Central to CB O2-sensing is their unique mitochondria but the link between mitochondrial inhibition and cellular stimulation is unresolved. The objective of this study was to evaluate if ex vivo intact CB nerve activity and in vivo whole body ventilatory responses to hypoxia were modified by alterations in succinate metabolism and mitochondrial ROS (mitoROS) generation in the rat. Application of diethyl succinate (DESucc) caused concentration-dependent increases in chemoafferent frequency measuring approximately 10-30% of that induced by severe hypoxia. Inhibition of mitochondrial succinate metabolism by dimethyl malonate (DMM) evoked basal excitation and attenuated the rise in chemoafferent activity in hypoxia. However, approximately 50% of the response to hypoxia was preserved. MitoTEMPO (MitoT) and 10-(6'-plastoquinonyl) decyltriphenylphosphonium (SKQ1) (mitochondrial antioxidants) decreased chemoafferent activity in hypoxia by approximately 20-50%. In awake animals, MitoT and SKQ1 attenuated the rise in respiratory frequency during hypoxia, and SKQ1 also significantly blunted the overall hypoxic ventilatory response (HVR) by approximately 20%. Thus, whilst the data support a role for succinate and mitoROS in CB and whole body O2-sensing in the rat, they are not the sole mediators. Treatment of the CB with mitochondrial selective antioxidants may offer a new approach for treating CB-related cardiovascular-respiratory disorders.